2020
DOI: 10.3389/fonc.2020.00417
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Node-Positive Non-small-Cell Lung Cancer Undergoing Sublobar Resection and the Role of Radiation in Its Management

Abstract: Purpose: To identify the incidence, preoperative risk factors, and prognosis associated with pathologically positive lymph node (pN+) in patients undergoing a sub-lobar resection (SLR). Methods: This is a retrospective study using the National Cancer Database (NCDB) from 2004 to 2014 analyzing SLR excluding those with any preoperative chemotherapy and/or radiation, follow-up <3 months, stage IV disease, or >1 tumor nodule. Multivariable modeling (MVA) was used to determine factors associated with overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This suboptimal staging is likely responsible for the observed reduced long-term oncological outcome of patients undergoing sublobar resections due to an upstaging failure effect. In fact, the authors ( 4 ) showed a nodal upstaging rate ranging from 7.6% for nodules under 2 cm to 15% for nodules over 2 cm treated with sublobar resection.…”
Section: Inadequate Sublobar Resectionmentioning
confidence: 99%
See 4 more Smart Citations
“…This suboptimal staging is likely responsible for the observed reduced long-term oncological outcome of patients undergoing sublobar resections due to an upstaging failure effect. In fact, the authors ( 4 ) showed a nodal upstaging rate ranging from 7.6% for nodules under 2 cm to 15% for nodules over 2 cm treated with sublobar resection.…”
Section: Inadequate Sublobar Resectionmentioning
confidence: 99%
“…It is known that anatomical segmentectomies performed by a minimally invasive approach are technically demanding procedures, with the expected result that much more wedge resections instead of anatomical segments have been done to avoid open surgery (4).…”
Section: Inadequate Sublobar Resectionmentioning
confidence: 99%
See 3 more Smart Citations